Dosa Manusia sebagai Ide Penciptaan Seni Lukis Kontemporer - Izzati, Mahmuda Aqidatul; Asa, Ferdian Ondira (AHKAM, 2023)
Sin is a violation of the law for actions that have been prescribed by religion. Humans have reason and mind to think logically, dynamically and can distinguish between good and bad actions. But often humans do not use their minds to think whether the actions taken are acts that are prohibited by religion or not, so that humans fall into sin. The purpose of making this final work is to visualize human sin in the form of a painting, as well as to remind again of human sins that should be avoided in life, because as a human being one should continue to live by strengthening faith and avoiding major sins that are prohibited by religion. The creation of the work was done using the acrylic paint technique on canvas measuring 100 x 100 and 100 x 120 cm. The creation method for the final work is carried out in stages, starting from the preparation, elaboration, synthesis, concept realization, and finishing stages in the work. After completing these stages, 10 paintings were created with the titles: : (1) Uang Haram; (2) Guna-guna; (3) Candu; (4) Kenikmatan Sesaat; (5) Perenggut Nyawa; (6) Air Mata Orang Tua; (7) Gantung diri; (8) Fitnah; (9) Penyekutu Tuhan; dan (10) Pencuri Hak anak yatim.